2020
DOI: 10.1021/acs.joc.0c00360
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene Catalysis Exploiting Oxidative Imine Umpolung for the Generation of Imidoyl Azoliums

Abstract: Although NHC-catalyzed umpolung of imines are known, the related reactions under oxidative conditions are limited. Described herein is the two-step process involving the initial formation of aldimines from the corresponding aldehydes and 2-amino benzyl alcohols followed by NHC-catalyzed cyclization proceeding via the imidoyl azoliums under oxidative conditions. The reaction allowed the synthesis of trifluoromethylated 3,1-benzoxazines in good yields and broad scope. The role of NHC in the intramolecular cycliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Extending the strategy, Biju and co-workers employed aldimines 207 derived from (2-aminophenyl)-2,2,2-trifluoroethanol and its derivatives 205 with aromatic aldehydes 191 for the synthesis of 3,1-benzoxazines 208 (Scheme 56). [82] The mechanism of the reaction was similar to the one discussed above and it was found that the initially generated aldimines go through an intra-molecular cyclization under oxidative NHC catalysis through the imidoyl azolium intermediates. The synthetic utility of this strategy was utilized for the synthesis of Efavirenz (Possessing anti HIV activity), employing this one-pot generation of 3,1-benzoxazines.…”
Section: Synthesis Of O N-heterocyclesmentioning
confidence: 61%
See 1 more Smart Citation
“…Extending the strategy, Biju and co-workers employed aldimines 207 derived from (2-aminophenyl)-2,2,2-trifluoroethanol and its derivatives 205 with aromatic aldehydes 191 for the synthesis of 3,1-benzoxazines 208 (Scheme 56). [82] The mechanism of the reaction was similar to the one discussed above and it was found that the initially generated aldimines go through an intra-molecular cyclization under oxidative NHC catalysis through the imidoyl azolium intermediates. The synthetic utility of this strategy was utilized for the synthesis of Efavirenz (Possessing anti HIV activity), employing this one-pot generation of 3,1-benzoxazines.…”
Section: Synthesis Of O N-heterocyclesmentioning
confidence: 61%
“…Intramolecular cyclization of aldimines 201 , synthesized from 2‐aminophenols and aromatic aldehydes under NHC catalysis resulted in the formation of 2‐aryl benzoxazoles 202 (Scheme 55). [82] Formation of aza‐breslow intermediate 203 obtained from aldimine and NHC was the key step of the reaction which on oxidation led to the generation of imidoyl azoliums 204 and further intramolecular cyclization gave the product in good yields.…”
Section: Figurementioning
confidence: 99%
“…Excellent reviews [26,27] on NHCs emphasized three major applications of these species, such as their coordination to transition metals, [28] coordination to pblock elements, [29] and as organocatalysts. [30][31][32][33] NHCs have been reported several times, e. g., [24,[34][35][36][37][38][39] and anionic NHCs appear less frequently in the literature. [23,[40][41][42]…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Biju and co-workers developed N-heterocyclic carbene (NHC) and p-toluenesulfonic acid (PTSA) catalyzed two-step synthesis of trifluoromethylated 3,1-benzoxazines through an annulation reaction of (2aminophenyl)-2,2,2-trifluoroethanol and aromatic aldehydes using toluene as solvent (Scheme 1b). 7 In their works, 2aminobenzyl alcohols provided three carbon atoms, one nitrogen atom, and one oxygen atom to the 3,1-benzoxazine framework. Aromatic aldehydes furnished one carbon atom to the C2 position of trifluoromethylated 3,1-benzoxazines.…”
Section: ■ Introductionmentioning
confidence: 99%